Nausea, Vomiting and Retching of Patients with Cervical Cancer undergoing Chemotherapy in Bali, Indonesia - Prapti, Ni Ketut Guru; Petpichetchian, Wongchan; Chongchareon, Wimonrat (Nurse Media Journal of Nursing, 2012)
Background: Nausea, vomiting and retching (NVR) was the frequently reported and troublesome adverse effect for patients receiving chemotherapy. Purpose: This study is a part of a larger study which aims to describe the NVR symptom experience in cervical cancer patients undergoing chemotherapy in Bali, Indonesia, and examine relationships with individual's risk factors. Method: Sixty-six patients with stage II and III cervical cancer receiving Paxus (Paclitaxel)-Cisplatin at the second or the third cycle were enrolled. NVR was measured by the Index of Nausea, Vomiting and Retching (INVR) at the second day of their chemotherapy. This current study included only patients with age ranged between 32 to 65 years (M = 47.15, SD = 9.64, min-max age 35 – 65 years). Result: The result showed that the NVR score was at a moderate level. Younger subjects (age 32-50 years old) reported significantly higher NVR scores than that of older subjects (age 51-65 years old) (t = 2.76, p = .007). The subjects with higher anxiety scores reported significantly higher NVR scores than those with lower anxiety scores (t = -2.41, p = .019). Subjects who had experience in motion sickness had significantly higher NVR scores (M = 12.69, SD = 2.60) than those who did not (M = 9.23, SD = 2.86) and the difference was statistically significant (t = 4.98, p <.01). Meanwhile, no significant difference was found between subjects who reported their expectation to have nausea and those who did not (t = 0.08, p = .94). Conclusion: The findings provide valuable information regarding NVR and the individual risk factors among patients with cervical cancer undergoing chemotherapy. Nurses should assess the anxiety level and a history of motion sickness of patients planned for chemotherapy and offer preventive interventions to prevent and control NVR occurrence and its distress.Keywords: cervical cancer, chemotherapy, nausea, vomiting and retching